Pembangunan model caj ruang bagi pengurusan ruang akademik yang optimum di Institusi Pengajian Tinggi, Malaysia - Ibrahim, Ihfasuziella (2012)
The cost of managing physical resources such as space in public university stands the second highest after the cost of staff salary. The management of physical space in university is somehow not easily manageable due to its dynamic nature which constantly changes with the increase in the number of students and staff. In view of that, an effective space management is an important agenda in order to be in line with the government direction for prudent spending. This research focuses on the utilization of space for teaching and learning at University Tun Hussein Onn of Malaysia by auditing, identifying and subsequently developing a Space Charging Model for an effective space management. The research employs a combination of quantitative and qualitative analysis approaches. The methodology of the study was conducted by auditing the utilization of space for teaching and learning administered by the Academic Centre, and subsequently comparing the finding against its actual usage. As much as six formulas had been used for auditing purposes which comprised of frequency of booking, frequency of use, utilization (occupied), optimum utilisation, used but not booked, booked but not used in determining the actual usage trend of the teaching and learning space. In developing the Model, the element of cost per square meter of each space has been computed and used as the basis of its development. The costs involved are that of management and operation, costs of utilities, maintenance, cleaning and landscape management. The audit analysis shows that some of the lecture rooms at the G3 Complex are underutilized. The results of interview however disclose that the space use is at optimum level and as such space inadequacy becomes an issue. The proposed Model is considered ideal for adoption in the public universities as it proposes that penalties be imposed to the head of centers who does not manage the space optimally. However, Space Charging Model is beneficial in educating users that space acquisition does not come free and that being the concern, it encourages the users to optimize its utilization either through sharing or renting it to other parties as it can generate income to the university.